EVERYDAY TALK: The Construction of Student Identities - Faishal Zakaria (Englisia: Journal of Language, Education, and Humanities, 2014)
This brief article discusses the notion of Identity Construction through everyday talk among interlocutors. In particular, this article discusses how I construct and co-construct my identities as a graduate student as I communicate with others. The re-search data used in this article was analysed through the framework of expert-novice constitution, co-construction, and legitimate peripheral participation. The data show their relevance to the notions of expert-novice, co-construction, and legitimate peripheral participation where the interlocutors are actively negotiating their identities as they try to claim their right to speak.